The Effects of Superimposed Whole-Body Electromyostimulation During Short-Term Strength Training on Physical Fitness in Physically Active Females: A Randomized Controlled Trial - Dörmann, Ulrike; Wirtz, Nicolas; Micke, Florian; Morat, Mareike; Kleinöder, Heinz; Donath, Lars (Frontiers in Physiology, 2019)
The aim of the study was to compare the effects of short-term strength training with and without superimposed Whole-Body Electromyostimulation (WB-EMS) on straight sprinting speed (SSS), change of direction speed (CODS), vertical (VJ) and horizontal jumping (HJ) as well as on strength and power in physically active females. Twenty-two active female participants (n = 22; mean ± SD: age: 20.5 ± 2.3 years; height: 171.9 ± 5.5 cm; body mass: 64.0 ± 8.2 kg; strength training experience 5.1 ± 3.6 years) were randomly assigned into 2 groups: strength training (S) or strength training with superimposed WB-EMS (S+E). Both groups trained twice a week over a period of 4 weeks and differed in the application of free weights or WB-EMS during 4 strength (e.g. split squats, glute-ham raises) and 5 sprinting and jumping exercises (e.g. side and box jumps, skippings). The WB-EMS impulse intensity was adjusted at 70% of individual maximal sustainable pain. SSS was tested via 30m sprinting, CODS by a T-run, VJ and HJ using 4 different jump tests at pre-, post- and re-test after a 2-week follow up. Maximal strength (Fmax) and power (Pmax) testings were conducted on the Leg Press (LP), Leg Extension (LE) and Leg Curl (LC) machine. Significant time*group interaction effects revealed significant decreases of contact time of the Drop Jump and split time of CODS (p ≤ .043; ηp² = .15-.25) for S (≤ 11.6%) compared to S+E (≤ 5.7%). Significant time effects (p < .024; ηp² = .17-.57) were observed in both groups for SSS (S+E: ≤ 6.3%; S: ≤ 8.0%) and CODS (S+E: ≤ 1.8%; S: ≤ 2.0%) at re-test, for jump test performances (S+E: ≤ 13.2%; S: ≤ 9.2%) as well as Fmax and Pmax for LE (S+E: ≤ 13.5%; S: ≤ 13.3%) and LC (S+E: ≤ 18.2%; S: ≤ 26.7%) at post- and re-test. The findings of this study indicate comparable effects of short-term strength training with and without superimposed WB-EMS on physical fitness in physically active females. Therefore, WB-EMS training could serve as a reasonable but no superior alternative to classic training regimes in females.